2007
DOI: 10.1161/01.atv.0000258794.57872.3f
|View full text |Cite
|
Sign up to set email alerts
|

IAP Survivin Regulates Atherosclerotic Macrophage Survival

Abstract: Objectives-Inflammatory macrophage apoptosis is critical to atherosclerotic plaque formation, but its mechanisms remain enigmatic. We hypothesized that inhibitor of apoptosis protein (IAP) survivin regulates macrophage death in atherosclerosis. Methods and Results-Western blot analysis revealed discrete survivin expression in human aorta lipid streaks but virtually none in advanced atherosclerotic plaques, despite increased XIAP and cIAP2 levels. Survivin was detected in CD68-positive macrophages infiltrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…These findings comply with the literature as Smac/DIABLO is a well-known IAP antagonist. Blanc-Brude et al [136] revealed discrete IAP survivin expression in human aorta lipid streaks but virtually none in advanced atherosclerotic plaques. The authors deduced that dysregulation of survivin expression caused by re-current oxLDL exposure may favor apoptosis in advanced atherosclerotic plaques despite up-regulated cIAP-2 and XIAP.…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 99%
“…These findings comply with the literature as Smac/DIABLO is a well-known IAP antagonist. Blanc-Brude et al [136] revealed discrete IAP survivin expression in human aorta lipid streaks but virtually none in advanced atherosclerotic plaques. The authors deduced that dysregulation of survivin expression caused by re-current oxLDL exposure may favor apoptosis in advanced atherosclerotic plaques despite up-regulated cIAP-2 and XIAP.…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 99%
“…While IAP protein blocks apoptosis via inhibition of effector caspases, oxidized low density lipoprotein (OxLDL) differentially regulates the members of IAP family [3,4]. OxLDL has been reported to decrease the expression of cellular inhibitor of apoptosis protein 1 (cIAP-1) in endothelial cells [5], and prolonged OxLDL treatment down-regulated Survivin expression in macrophages [6]. In advanced atherosclerotic lesions, Survivin expression is absent despite an increase in both x-linked inhibitor of apoptosis protein (XIAP) and cellular inhibitor of apoptosis protein 2 (cIAP2) [6].…”
Section: Introductionmentioning
confidence: 99%
“…OxLDL has been reported to decrease the expression of cellular inhibitor of apoptosis protein 1 (cIAP-1) in endothelial cells [5], and prolonged OxLDL treatment down-regulated Survivin expression in macrophages [6]. In advanced atherosclerotic lesions, Survivin expression is absent despite an increase in both x-linked inhibitor of apoptosis protein (XIAP) and cellular inhibitor of apoptosis protein 2 (cIAP2) [6]. Whether OxLDL induces apoptosis via down-regulation of Survivin expression in vascular endothelial cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these data highlight the complexity of atheropathogenesis, with the likelihood that a multiple hit hypothesis rather than a single event is important in terms of disease progression. Balancing pro-apototic factors are a series of inhibitors of this process which include: Bcl-2 [107], macrophage colony-stimulating factor (M-CSF) [108], tissue inhibitors of metalloproteinases (TIMPs) [109], survivin [108], TOSO [110], FLICE-like inhibitory protein (FLIP) [111], Bfl-1, and Mcl-1 [112]. The importance of considering the temporal aspects of macrophage apoptosis in atherosclerosis is illustrated by recent work on survivin, a caspase inhibitor of the inhibitors of apoptosis (IAP) family, which is transcribed specifically during mitosis and is usually absent in normal adult tissues.…”
Section: Macrovascular Complications-cardiovascular Disease and Macromentioning
confidence: 99%